DISSATISFACTION WITH BODY IMAGE IN COLLEGE IN UNIVERSITARY STUDENTS (Fiep Bulletin - online, 2014)
Objective: The aim of this study was (1) analyzethebodydissatisfaction in academics (2) identifymethodsemployed for thisreview. Method: wereconsultationsthefollowingdatabases BIREME, LILACS AND MEDLINE, usingthekeywords BODY IMAGE, BODY DISSATISFACTION AND UNIVERSITY STUDENTS. The periodofanalysiswas 2000-2013. Results: selected 28 articles in descriptivestudies, which, showed (1) growingscientificproductiononthesubject in recentyears. (2) Therewas a varietyofinstrumentsemployedbyhighlightingthe BSQ, EAT AND TEST OF SILHOUETTES. AmongthestudiesthatusedtheBody Mass Index (BMI), 50% found correlation with body dissatisfaction. Conclusion: there is agrowing interest of the scientific literatureon better under standing the body dissatisfaction in university students. In the case of future professionals, theim pactof the finding son the body dissatisfaction is highly relevant in the light of the need for management psychotherapy this framework. There is a need to promote ther apeuticaction saiming to deal with the body dissatisfaction and preventing risk behaviors
Keywords: Body dissatisfaction; academics; bodyimage